Determination of Chlorogenic Acid, Caffeine and Antioxidant Capacities in Turkish-Style Coffee Bean Samples - Haydar Özpınar; Johanna Rebekka Morche; Harshadrai M. Rawel (Proceedings)
For many years, coffee has maintained its place in Turkey as Turkish coffee (i.e., boiled, finely ground, unfiltered), and has become globally recognized. However, in recent years, especially for young people, filter coffee has become more popular, instead of Turkish coffee. As is generally known today, climatic conditions and processing techniques have an impact on the constituents of coffee. It is also thought that the finer grinding of Turkish coffee may affect the variability of the coffee contents. The mentioned popularity of the coffee beverage is also causing an increased interest in its nutritional and functional properties as well as its chemical constituents. Therefore, an analytical determination of the coffee ingredients is essential. Taste may be the most important criterion for coffee consumption for most consumers, but the health benefits should not be underestimated. Coffee has an antioxidant effect due to the phenolic compounds present, such as chlorogenic acid. It is also known to prevent cellular damage, which has led to increased interest in its antioxidant properties. The aim of this study was to investigate the total chlorogenic acids (CQAs), caffeine and antioxidant capacities of coffees commonly consumed in Turkey. For this purpose, three green and three roasted coffee samples of the Coffea arabica, Coffea canephora and Coffea liberica varieties were selected for this study and characterized. Different targeted mass spectrometry (LC-MS/MS) methods were developed to encompass the above-mentioned ingredients. The roasting process significantly increased the caffeine content in three roasted samples compared to green coffees. These values ranged from 1.2 g per 100 g dry mass (DM) in green coffees to 2.6 g per 100 g DM in roasted coffees. It could be shown that the most dominant CQA contained was 5-CQA. While the amount of CQA in green coffees is approximately 49–64%, it decreases down to 33–41%, by isomer conversion partly, to 4-CQA and 3-CQA in the roasting process. The highest value was found at 3.5 g/100 g DM. The highest value for the antioxidation capacity was 4.4 g ascorbic acid equivalents/100 g DM roasted coffee and the lowest value was 2.4 g/100 g DM in green coffee. This study was the first attempt to demonstrate the presence of different CQAs, caffeine and antioxidation capacity in coffee beans from the market in Turkey and needs to be followed up further with a larger sample size in future studies.